The formation, development and contribution of the New Ideals in Education conferences, 1914–1937. Issue 4 (4th July 2017) - Howlett, John
Abstract: This paper seeks to explore the development, impact and contribution made by the New Ideals in Education conferences, which were held between 1914 and 1937. In particular, it will examine how the group emerged from the English Montessori Society and forged an identity of its own based on the thoughts and ideas of its two major protagonists: Edmond Holmes and the Earl of Lytton. This was especially manifest in its commitment to a form of non-partisanship that sought to be inclusive as possible towards those agitating for liberty within the classroom. The paper will also examine the profound impact played by the First World War, whose events were a catalyst not merely for impelling the group to discuss and showcase practice but also how this could be applied in the reconstruction process. In so doing it will chart the evolution of the New Ideals movement, which fizzled out just prior to the Second World War.